Rekayasa Didaktis untuk Mengembangkan Flipbook Bangun Ruang dalam Rangka Meningkatkan Kemampuan Berpikir Kreatif Siswa Sekolah Dasar - Uzlifatul Hasanah; Tatag Yuli Eko Siswono; Rooselyna Ekawati (LP. Ma'arif Janggan Magetan, 2023)
A whole attention in didactic situations that might occur/ influence is the strength of didactic engineering as a research design for the development of mathematics learning media. The results of the epistimological obstacle and didactic obstacle analysis of students' creative thinking abilities in geometric material showed a gap between expectations and reality. Based on the results of the a priori analysis, flipbook media is appropriate to be used as one of the media development innovations to improve elementary students' creative thinking skills. Armed with completeness and a clear structure, this media got implementation results that show valid, practical as learning media and and not yet effective because students need time to adapt a new media but it can be seen that there was an increase from the value of presentation student who pass the minimum learning completeness criteria from 0% up to 46%. Based on the results of the a posteriori analysis which is validated by the results of the a priori analysis, it showed that this media can be used to improve students' creative thinking skills in terms of learning outcomes and other didactic phenomena during and after using the media